Safety awareness among pre-service teachers of technical and vocational education in Malaysia - Usman, Ibrahim; Mat Rashid, Abdullah (International Digital Organization for Scientific Information, 2014)
The main purpose of this study is to investigate the level of safety awareness among pre-service teachers in technical and vocational education. This study focus on tools and equipment arrangement, uses of personal protective devices and years of study in the program in regards to safety awareness. This study utilized survey that was administered to 196 samples of technical and vocational pre-service teachers in Malaysia. The findings shows mean of safety awareness, tools and equipment arrangement are moderate among pre-service teachers. Meanwhile, finding shows that there are significant differences of safety awareness between pre-service teachers’ years of study.